TINJAUAN YURIDIS TERHADAP PELANGGARAN HAK ASASI MANUSIA YANG DILAKUKAN OLEH APARAT PENEGAK HUKUM KEPADA DEMONSTRAN DI KOTA TANGERANG BERDASARKAN TEORI SOSIOLOGI HUKUM - Binsar Mariz Juan Alfredo Hutabarat; Mamay Komariah; Ratna Indayatun (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
Human rights are every human's. His existence is an absolute thing. But in application, human rights abuses continue to occur. Human rights abuses are also carried out by law enforcement officials to demonstrators. What factors have led to the action of human rights abuses by law enforcement officials to demonstrators on the basis of law sociology theory and how the law's certainty to law enforcement officials on human rights became the object of study. Then the study may be useful for the development of law science, law enforcement officers as well as for demonstrators or communities. The study adopted an empirical juridical approach. Studies are conducted by conducting interviews with relevant sources as well as books and laws as research guides. The theories used in this study are the theories of law sociology, of certainty of law and of justice. Research suggests that the spontaneous process of human rights abuses by law enforcement officials has been carried out by demonstrators. Legal certainty for law enforcement agencies that violate human rights has also been done according to action. However, law enforcement officials need to be more patient with guarding demonstrations in order to resort to violence or unlawful behavior of any thinks. Keywords: Human Rights; Law Enforcement Officials; Demonstrators.